2016
DOI: 10.1016/j.ajhg.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Chad Genetic Diversity Reveals an African History Marked by Multiple Holocene Eurasian Migrations

Abstract: Understanding human genetic diversity in Africa is important for interpreting the evolution of all humans, yet vast regions in Africa, such as Chad, remain genetically poorly investigated. Here, we use genotype data from 480 samples from Chad, the Near East, and southern Europe, as well as whole-genome sequencing from 19 of them, to show that many populations today derive their genomes from ancient African-Eurasian admixtures. We found evidence of early Eurasian backflow to Africa in people speaking the unclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 39 publications
2
49
1
Order By: Relevance
“…Our data on uniparental markers, on the other hand, indicate differences in the population histories of male and female subpopulations. It has been well established that in the populations of eastern and central Sahel there is a discernible Eurasian genetic component introduced over a long period of time by numerous migration events from different non‐African regions (Galego Llorente et al, ; Haber et al, ; Pickrell et al, ). Successive waves of migration are clearly reflected in both maternal and paternal genetic pools (Bučková et al, ; Černý et al, ; Podgorná et al, ; Shriner & Rotimi, ) and also in autosomal datasets as shown by allele frequency based methods (Triska et al, ; Vicente et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data on uniparental markers, on the other hand, indicate differences in the population histories of male and female subpopulations. It has been well established that in the populations of eastern and central Sahel there is a discernible Eurasian genetic component introduced over a long period of time by numerous migration events from different non‐African regions (Galego Llorente et al, ; Haber et al, ; Pickrell et al, ). Successive waves of migration are clearly reflected in both maternal and paternal genetic pools (Bučková et al, ; Černý et al, ; Podgorná et al, ; Shriner & Rotimi, ) and also in autosomal datasets as shown by allele frequency based methods (Triska et al, ; Vicente et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The study of population structure allows assigning individuals to distinct ethnic groups cohabiting a particular region (Liu et al 2018), investigating migrations from the origin of admixed populations (Haber et al 2016), and quantifying and characterising confounding due to shared genetic ancestry in association studies (Wang et al 2018). In humans, genetic variation is not randomly distributed across the world because of non-random mating between individuals, who tend to marry within their community, often driven by physical proximity (Schneider and Peischl 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we sequenced whole-genomes of 99 present-day Lebanese individuals to ~8x coverage on an Illumina HiSeq 2500 using 2× 100 bp reads. We merged the low-coverage Lebanese data with four high-coverage (30x) Lebanese samples, 26 1000 Genomes Project phase 3 CEU, YRI, and CHB populations, 27 and sequence data previously published from regional populations (Egyptians, Ethiopians and Greeks). 1; 26 Raw calls were generated using bcftools (bcftools mpileup -C50 -pm3 -F0.2 -d10000 | bcftools call -mv, version 1.2-239-g8749475) and filtered to include only SNPs with the minimum of 2 alternate alleles in at least one population and site quality larger than 10; we excluded sites with a minimum per-population HWE and total HWE less than 0.01 28 and sites within 3bp of an indel.…”
mentioning
confidence: 99%